Pengaruh Sistem Pengukuran Kinerja Dan Komitmen Karyawan Sebagai Variabel Intervening Terhadap Kinerja Karyawan Di Coffee Shop Kota Metro - Dwi Hanaya, Silva; Suyanto, Suyanto; Padwa Sari, Gustin (Expensive: Jurnal Akuntansi dan Keuangan, 2024)
This study aims to analyze the performance measurement system and employee commitment as a mediating variable for employee performance in Metro City coffee shops. This type of research uses primary data through questionnaires and the population in this study is 555 employees then the sampling technique in the study uses the formula of the minimum sample number for SEM (indicator x 10) then the number of samples is 130 respondents. The results of this study show that the performance measurement system has no effect on employee performance, the performance measurement system has an effect on employee commitment, and employee commitment has an effect on employee performance, and employee commitment can mediate the relationship between the performance measurement system and employee performance in Metro City coffee shops